2021
DOI: 10.1055/s-0041-1739446
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices of Parents on Early Childhood Caries in Qatar—A Questionnaire Study

Abstract: Objectives The aims of the present study were to evaluate the level of knowledge, attitudes, and practices (KAP) toward early childhood caries (ECC) in a group of Qatari parents and to assess the association of sociodemographic factors on their KAP. Materials and Methods A cross-sectional study which was based on a piloted self-administered questionnaire was conveniently distributed to parents who attended the Pediatric Dentistry Section, Hamad Dental Center (HDC), Doha, Qatar. The questionnaire comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 41 publications
1
13
1
Order By: Relevance
“…Findings also revealed that a maximum of the mothers had good oral hygiene practice, but Krishnan et al found that 13.7% of the mothers had good practice (29). A significant association was present between knowledge level and age of the mothers in contrast with the study of Al-Jaber et al (32). Likewise educational status and monthly family income are significantly associated with knowledge level.…”
Section: Discussioncontrasting
confidence: 93%
“…Findings also revealed that a maximum of the mothers had good oral hygiene practice, but Krishnan et al found that 13.7% of the mothers had good practice (29). A significant association was present between knowledge level and age of the mothers in contrast with the study of Al-Jaber et al (32). Likewise educational status and monthly family income are significantly associated with knowledge level.…”
Section: Discussioncontrasting
confidence: 93%
“…[ 25 , 26 ] and varies greatly across the globe. It has been reported that parents with an academic degree had superior knowledge about better oral hygiene practices than parents with only school education [ 21 , 26 , 27 , 28 ]. These results are concurrent with our study where 50-65% mothers and 60–65% fathers had no university education.…”
Section: Discussionmentioning
confidence: 99%
“…The better level of KAP about oral hygiene among mothers is directly related to better oral health and less chances of dental caries among their children (Al-Jaber et al, 2021). A systemic review also reported that children of mothers with poor KAP had higher risk of dental caries (Iqbal et al, 2022).…”
Section: Mothers Attitude Regarding Children's Oral Healthmentioning
confidence: 99%